Biochar use in a legume–rice rotation system: effects on soil fertility and crop performance. Issue 2 (1st February 2016) - Partey, Samuel T.; Saito, Kazuki; Preziosi, Richard F.; Robson, Geoffrey D.
Abstract : The aim of this study was to determine whether by applying biochar, it is possible to augment the beneficial effects of legume–crop rotation systems on soil fertility and crop performance. Repeated experiments were established in 2012 and 2013 in South-western Benin using a split-split plot design. Two legumes, Mucuna pruriens (mucuna) and Vigna unguiculata (cowpea), were planted for 42 days on biochar-amended and unamended plots and subsequently cut and applied as mulch 5 days before planting rice. Rice plants were either fertilized or not using a fertilizer rate of 60, 30, and 30 kg ha −1 of N, P2 O5, and K2 O, respectively. The results showed that the application of legume green manures and fertilizer, either singly or in combination, improved soil nutrient availability, CEC, shoot yield, and grain yield of rice on both biochar-amended and unamended plots. However, the effect was significantly ( p  < 0.05) greater on biochar-amended plots. The mean grain yield for all cropping seasons was 1.8 t ha −1 for biochar-amended plots and 1.3 t ha −1 for unamended plots. The greater grain yield of rice on biochar-amended plots was associated with improved soil fertility and increased N uptake.